The academic outcomes of working memory and metacognitive strategy training in children: A double‐blind randomized controlled trial. Issue 4 (27th June 2019) - Jones, Jonathan S.; Milton, Fraser; Mostazir, Mohammod; Adlam, Anna R.
Abstract: Working memory training has been shown to improve performance on untrained working memory tasks in typically developing children, at least when compared to non‐adaptive training; however, there is little evidence that it improves academic outcomes. The lack of transfer to academic outcomes may be because children are only learning skills and strategies in a very narrow context, which they are unable to apply to other tasks. Metacognitive strategy interventions, which promote metacognitive awareness and teach children general strategies that can be used on a variety of tasks, may be a crucial missing link in this regard. In this double‐blind randomized controlled trial, 95 typically developing children aged 9–14 years were allocated to three cognitive training programmes that were conducted daily after‐school. One group received Cogmed working memory training, another group received concurrent Cogmed and metacognitive strategy training, and the control group received adaptive visual search training, which better controls for expectancy and motivation than non‐adaptive training. Children were assessed on four working memory tasks, reading comprehension, and mathematical reasoning before, immediately after, and 3 months after training. Working memory training improved working memory and mathematical reasoning relative to the control group. The improvements in working memory were maintained 3 months later, and these were significantly greater for the group that received metacognitive strategy training, compared to working memory training alone. Working memory training is a potentially effective educational intervention when provided in addition to school; however, future research will need to investigate ways to maintain academic improvements long term and to optimize metacognitive strategy training to promote far‐transfer. A video abstract of this article can be viewed at https://youtu.be/-7MML48ZFgw Abstract : Working memory training in schools was found to improve children's working memory performance and mathematical reasoning ability. Working memory benefits were maintained three months later and were significantly greater for children that received additional metacognitive strategy training.